Oral Kavitede Leiomyom: Vaka Sunumu ve Literatür Taraması - (:unkn) unknown (My University, 2017)
Leiomyoma en sık kadın genital sisteminde olmak üzere herhangi bir bölgede bulunabilen benign düz kas tümörüdür. Leiomyomalar oral kavitede yaygın olmamakla beraber dil, dudak ve palatinal mukozada izlenebilir. Bu olgu sunumunun amacı leiomyoma saptanan bir bayan hastayı sunarak literatür taranmasıdır. 35 yaşında bir bayan hastada sağ mandibular molar bölgede vestibül alveol mukozasında yaklaşık bir yıldır sınırlı, asemptomatik yumuşak doku kitlesi mevcut olduğu saptanmıştır. Lokal anestezi ile eksizyonel biyopsi uygulanmış ve alınan örnek histopatolojik incelemeye gönderilmiştir. Histopatolojik tanı leiomyoma idi. Leiomyomayı diğer mezenşimal kaynaklı tümörlerden klinik olarak ayırmak oldukça zordur. Kesin tanı histolojik muayene ile olmalı ve bu lezyonların tedavisi cerrahi olarak yapılmalıdır

Leiomyoma is a benign smooth muscle tumor that can be observed at any region but is mostly observed in the female genital tract. Although leiomyomas are uncommon in the oral cavity, they are usually observed on the lips, tongue, and palate. Here we present a case report of leiomyoma in a female patient along with the literature review. A 35-year-old Turkish female presented with a 1-year history of a well-delineated, asymptomatic, and soft mass on the vestibule alveolar mucosa of the right mandibular molar region. Under local anesthesia, excisional biopsy was performed and the specimen was sent for histopathological examination. The histopathological diagnosis was leiomyoma. Based on clinical appearance, it is very challenging to distinguish a leiomyoma from other mesenchymal-origin tumors. Histological analysis determined the final diagnosis of oral leiomyoma, and surgery was performed because it was the only option for the treatment of these lesions
Leiomyoma of Oral Cavity: Case Report and Literature Review
Keywords: Tıbbi Araştırmalar Deneysel